Effects of contrast administration on cardiac MRI volumetric, flow and pulse wave velocity quantification using manual and software-based analysis - Fathi, Amir (Br J Radiol, 2018)
OBJECTIVE: The aim of the current study was to determine the effects of gadolinium contrast agent on right (RV) and left ventricular (LV) volumetric, aortic flow and pulse wave velocity (PWV) quantification using manual, semi-automatic and fully automatic analysis techniques. METHODS: 61 participants free from known cardiovascular disease were recruited. Cardiac MR was performed on a 3 T scanner. A balanced steady-state free precession stack was acquired of the ventricles with phase contrast imaging of the aorta performed pre- and post-administration of 10 ml 0.5 mmol ml(−1) gadoterate meglumine. The images were analysed manually, and using a semi-automated and a fully automated technique. RESULTS: 54 completed the study. Gadolinium-based contrast administration significantly increase the signal-to-noise ratio (pre: 830 ± 398 vs post: 1028 ± 540, p = 0.003) with no significant change in contrast-to-noise ratio (pre: 583 ± 302 vs post: 559 ± 346, p = 0.54). On LV analysis, post-contrast analysis yielded significantly higher end systolic volume (54 ± 20 vs 57 ± 18 ml, p = 0.04), and lower ejection fraction (59 ± 9 vs 57 ± 8%, p = 0.023). On RV analysis, gadolinium contrast resulted in no significant differences. Similar results were seen using the semi-automated and fully-automated techniques but with a larger magnitude of difference. Conversely, using both manual and software analysis aortic flow and PWV quantification proved robust to the effects of contrast agent producing only small non-significant differences. CONCLUSION: Gadolinium contrast administration significantly alters LV endocardial contour detection with this effect amplified when using semi-automated analysis techniques. In comparison, RV and PWV analysis is robust to these effects. ADVANCES IN KNOWLEDGE: Contrast administration alters LV quantification but not flow analysis. However, these differences are small.